The use of real-time PCR (qPCR) for the diagnosis of bovine herpes virus 5 in formalin-fixed, paraffin-embedded bovine brain samples identified as bovine unspecific encephalitis - Pedraza-Ordoñez, Francisco [UNESP]; Yamatogi, Ricardo Seidi [UNESP]; Araújo Júnior, João Pessoa [UNESP]; Rocha, Noeme Souza [UNESP]; Alessi, Antonio Carlos [UNESP] (OMICS International, 2013)
Background: Bovine herpes virus 5 (BoHV-5) is a neurovirulent alpha herpes virus that causes fatal meningoencephalitis and huge economic losses in the livestock and associated industries worldwide; its diagnosis in the laboratory is essential for disease control, immunologic surveillance and effective monitoring programs in endemic areas. Materials and Methods: In this study, brain samples from 21 Colombian cattle that died of neurological disease, were negative for rabies and were diagnosed with nonspecific encephalitis were processed by real-time PCR (qPCR) in the laboratory of virology at the Institute of Biosciences, Sao Paulo State University, Brazil, to detect BoHV-5 genetic material in tissue preserved in paraffin blocks. Tissues were considered positive for BoHV-5 if amplification occurred at or before 30 PCR cycles, inconclusive if amplification occurred between 30 and 40 cycles and negative otherwise. Results and Conclusion: Two cases were positive, demonstrating that qPCR may be useful for confirming herpes encephalitis in acid formalin-fixed tissues with an inconclusive diagnosis.
Keywords: Bovine herpes virus 5; Real-time PCR; Diagnosis; BoHV-5